Liquid Crystal and Fiber Elements for Photonics and Their Theoretical Characterization - Chigrinov, Vladimir (Photonics Letters of Poland, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]-->A brief editorial overview of the current issue is presented. This special issue of Photonics Letters of Poland devoted to liquid crystal and fiber elements for photonics contains 12 letters showing a wide range of photonics elements, including their theoretical characterization.<!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->